Grendon and the emergence of forensic therapeutic communities: developments in research and practice - Shuker, Richard (Wiley-Blackwell, 2010)
(Publisher-supplied data) 1 Prison-based democratic therapeutic communities: Introducing HMP Grendon Alisa Stevens 2 Dovegate Therapeutic Community: Bid, birth, growth and survival Eric Cullen and Alan Miller 3 The Van der Hoeven Clinic: A flexible and innovative forensic psychiatric hospital based on therapeutic community principles. Judith de Boer- van Schaik and Frans Deerks 4 Concept therapeutic communities in America and elsewhere Douglas Lipton 5 The development of an adapted therapeutic community within a DSPD setting John Shine 6 Putting principles into practice: The "Good Lives" model Michael Brooks 7 Personality disorder: Using therapeutic communities as an integrative approach to addressing risk Richard Shuker 8 Psychodrama as part of core therapy at HMP Grendon Jinnie Jeffreys 9 Art therapy as a means of assessing readiness for treatment Bill Wylie 10 Undertaking therapy at Grendon with men who have committed sexual offences Geraldine Akerman 11 Reflections on Grendon: Interviews with men who are about to leave Elizabeth Sullivan 12 "This can't be real": Continuity at Grendon Lorna Rhodes 13 The experience of officers in a therapeutic community prison: An interpretive phenomenological analysis James McManus 14 Emotional influence and empathy in prison-based communities Karen Niven, David Holman and Peter Totterdell 15 The quality of life of prisoners and staff at Grendon Guy Shefer 16 Suicide and self-harm at Grendon Adrienne Rivlin 17 Changes in prison offending among residents of a prison-based therapeutic community Margaret Newton 18 PROQ Changes in interpersonal relating following treatment at Grendon Michelle Newberry and Richard Shuker 19 The experiences of Black and minority ethnic (BME) prisoners in a therapeutic community prison Michelle Newberry 20 Research in prisons Martin Fisher, Carol Ireland and Elizabeth Sullivan